A LABORATORY STUDY ON THE LIFE CYCLE OF ISCHNURA EVANSI (MORTON)(ODONATA : COENAGRIONIDAE) FROM A POND AT BASRAH. - MARZOQ, M.KH.; Ali, M. H.; Annon, M. R. (Iraqi Journal of Aquaculture, 2022)
The life cycle of Ischnura evansi (Morton) from Basrah region has been studied under laboratory conditions . Females layed their eggs on the stems of the submerged portions of Bacopa monniera . Hatching occurred at a temperature limits between 12 and 40 °C. The embryonic development was compeleted within 31 days at 12 °C and 7 days at 40 °C water temperature . Larval development was rapid and signficantly corelated with high temperature . Instar duration were increased with the progress of age while discreasing with the rising of temperature. After hatching the insect showed 13 instar before the attaining of the adult stage. The total period from egg to adult were between 197 and 278 days at a 40 °C and 25 °C respectively .